Tropaeolaceae endémicas del Perú - León, Blanca (2006)
This is the «mashua» family. The Tropaeolaceae are represented in Peru by one genus, Tropaeolum, and 24 species (Brako & Zarucchi, 1993), all herbs and vines. Here we recognize 10 endemic species, which are found mainly in Very Humid Montane Forests and Mesoandean regions, between 1800 and 3200 m elevation. Only one endemic has been recorded within Peru’s protected areas system.